Ready or Not: Examining Self-Reported Readiness for Behavior Change at Intake Assessment for Adults With an Eating Disorder. Issue 2 (March 2020) - Hudson, Chloe C.; Mac Neil, Brad A.
We explored whether a single-item self-report measure (i.e., the Readiness Ruler) was an appropriate measure of treatment engagement in adult outpatients with eating disorders. In total, 108 women diagnosed with an eating disorder completed the Readiness Ruler and measures of symptom severity at intake to a hospital-based outpatient treatment program. Treatment engagement was operationalized as attendance to a minimum of one session of a cognitive-behavioral therapy (CBT) treatment group, the number of CBT group sessions attended, and whether the participants dropped out of the CBT group prematurely. Results suggest that the Readiness Ruler was not associated with attending the CBT group. Among the participants who attended the program, the Readiness Ruler was not associated with the number of CBT group sessions attended or CBT group dropout. Higher Readiness Ruler score was associated with more severe symptomatology. In conclusion, the Readiness Ruler may not be a good predictor of CBT group treatment engagement for individuals with eating disorders and may instead be a proxy for symptom severity.